Pengaruh Penyemprotan Ekstrak Daun Teh Hijau (Camellia sinensis) Terhadap Stabilitas Dimensi Hasil Cetakan Alginat - Septa S. Arini; Indah Saraswati; Astika W. Utomo; Oedijani Santoso (SAINS : Jurnal Kimia & Pendidikan Kimia, 2021)
Alginate has imbibition and sineresion properties. Green tea leaves (Camellia Sinensis) contain phenols which are antibacterial and can minimize changes in dimensional stability. This study aims to analyze the effect of 50% green tea leaf extract as a disinfectant on the dimensional stability of the alginate impression sprayed at different times. Post-test only experimental laboratory research. Dimensional stability is measured by the difference between the anteroposterior (A'-B ') and mediolateral (B'-C') die stone and the master die using digital calipers with an accuracy of 0.01 mm. Data on anteroposterior and mediolateral dimensions were analyzed using the One Way Anova test, followed by the Post Hoc LSD test. The results of the One Way Anova test for anteroposterior and mediolateral dimensions were significant (p = 0.00). The results of the Post Hoc LSD test for the anteroposterior dimension were significant, while for the mediolateral dimension, the results were not significant between the K1 and K2 and P1 groups. The smallest dimensional stability changes in the anteroposterior and mediolateral dimensions occurs in the alginateimpression group sprayed with green tea leaf extract stored for 5 and 10 minutes.